Energy optimization in integrated pulp and paper mills with recourse to environmental benefits - Pharande, V. A.; Asthana, S. R.; Saini, D. R.; Kaul, S. N. (Journal of Scientific & Industrial Research, 2011)
This study focuses on energy optimization in evaporator and digester of integrated pulp and paper mills in India, and recommends application of 7 effects/plates evaporator in place of 5 effects/plates normally used. Steam economy resulting from this modification is definitely more than 7. Pinch technology is found suitable for optimization of controlled parameters in the digester. Using recommendations, total energy savings was observed in West Coast Paper Mill (11.74%) and Star Paper Mill (12.97%). Environmental benefits that will accrue in terms of reductions in emissions are: SPM, 46464-48664 TPA; SO(2), 1045 kg/annum; H(2)S, 55,020 kg/annum; and CO(2), 13612 TPA.
Keywords: Air emissions; Digester; Evaporator; Pinch technology; Steam economy

Continuous precipitation of calcium carbonate using sonochemical reactor - Shirsath, S. R.; Sonawane, S. H.; Saini, D. R.; Pandit, A. B. (Ultrasonics Sonochemistry, 2015)
The continuous production of calcium carbonate (CaCO3) by precipitation method at room temperature was carried out in a stirred reactor under ultrasonic environment and was compared with the conventional stirring method. The effect of various operating parameters such as Ca(OH)(2) slurry concentration, CO2 flow rate and Ca(OH)(2) slurry flow rate on the particle size of CaCO3 was investigated. The calcium carbonate particles were characterized by Fourier transform infrared (FTIR), wide angle X-ray diffraction (WXRD) and particle size. The morphology was studied by using scanning electron microscopic (SEM) images. The particle size obtained in the presence of ultrasonic environment was found to be smaller as compared to conventional stirring method. The particle size is found to be reduced with an increase in the concentrations of Ca(OH)(2) and increased with increasing CO2 flow rate for both the methods. The slurry flow rate had a major effect on the particle size and the particle size decreased with increased slurry flow rate. Only calcite phase of CaCO3 was predominantly present as confirmed by the characterization techniques for both the preparation methods. In most of the cases rhombohedral calcite particles were observed. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Calcite; Crystal growth; Morphology; Nucleation; Particle size; Ultrasound

Removal of methylene blue (MB) dye from water environment by processed Jowar Stalk [Sorghum bicolor (L.) Moench] adsorbent - Dod, Ramesh; Banerjee, Goutam; Saini, D. R. (Clean Technologies and Environmental Policy, 2015)
The present paper discusses the results of the study of adsorption of methylene blue on activated carbon, derived from cheap and abundantly available agro-residue of Jowar Stalk (JS) [Sorghum bicolor (L.) Moench] on suitable heat and acid treatment. The physico-chemical and morphological characteristics of processed carbon of JS origin were studied using X-ray diffraction, scanning electron microscopy, Brunauer, Emmett and Teller surface area, and Fourier transform infrared spectrophotometry analyses. The batch studies revealed optimum values of adsorption parameters such as pH, adsorbent dosage, agitation speed, grain size, temperature, and contact time as 7, 1.5 g l(-1), 200 rpm, finer than 75 A mu m, 30 A degrees C, and 7 h, respectively. The adsorption isotherm data were best described by Langmuir isotherm model with a maximum adsorption capacity of 176.05 mg MB g(-1) JS activated carbon at 30 A degrees C, which is higher than that available with adsorbents used by past researchers. In terms of cost-effectiveness, JS carbon shows its superiority over commercially available carbon.
Keywords: Adsorption; Isotherms; kinetics; Methylene blue; Processed Jowar Stalk [Sorghum bicolor (L.) Moench]

Intensification of extraction of curcumin from Curcuma amada using ultrasound assisted approach: Effect of different operating parameters - Shirsath, S. R.; Sable, S. S.; Gaikwad, S. G.; Sonawane, S. H.; Saini, D. R.; Gogate, P. R. (Ultrasonic Sonochemistry, 2017)
Curcumin, a dietary phytochemical, has been extracted from rhizomes of Curcuma amada using ultrasound assisted extraction (UAE) and the results compared with the conventional extraction approach to establish the process intensification benefits. The effect of operating parameters such as type of solvent, extraction time, extraction temperature, solid to solvent ratio, particle size and ultrasonic power on the extraction yield have been investigated in details for the approach UAE. The maximum extraction yield as 72% was obtained in 1 h under optimized conditions of 35 degrees C temperature, solid to solvent ratio of 1:25, particle size of 0.09 mm, ultrasonic power of 250 W and ultrasound frequency of 22 kHz with ethanol as the solvent. The obtained yield was significantly higher as compared to the batch extraction where only about 62% yield was achieved in 8 h of treatment. Peleg's model was used to describe the kinetics of UAE and the model showed a good agreement with the experimental results. Overall, ultrasound has been established to be a green process for extraction of curcumin with benefits of reduction in time as compared to batch extraction and the operating temperature as compared to Soxhlet extraction.
Keywords: Acrylamide; Cavitation; Curcumin Extraction; Design; Enhancement; Functionalized Silica; kinetics; Microwave; Nanoparticles; Natural-products; Optimization; Phenolic-compounds; Process Intensification; Solid-liquid Extraction; Ultrasound